Synthesis of heterogeneous photo-Fenton catalyst from iron rust and its application to degradation of Acid Red 97 in aqueous medium. Issue 3 (June 2022) - Ghazzaf, H.; Nechchadi, B.; Jouali, A.; Salhi, A.; El Krati, M.; Tahiri, S.
Abstract: In this work, magnetic nanoparticles were synthesized from iron rust waste and used as a catalyst for photo-Fenton degradation of Acid red 97 (AR97). The morphology and size of Fe3 O4 nanoparticles could be controlled by adding an appropriate amount of water as co-solvent in solvothermal treatment. For a comparative study, α-FeOOH and α-Fe2 O3 with nanorod shape were also prepared from iron rust and employed as photo-Fenton catalyst. The photo-Fenton degradation results showed that the prepared Fe3 O4 nanoparticles with spherical-like shape possessed higher catalytic activity than octahedral-shaped Fe3 O4, α-FeOOH, and α-Fe2 O3 . It was demonstrated that the synergetic effect between H2 O2 and oxalic acid (OA) led to an improvement in the catalytic efficiency of the photo-Fenton system towards AR97 degradation in awide pH range. At 180 min, about 81% of total organic carbon (TOC) was removed. Thus, the mineralization of organic matter is strongly involved during the photo-Fenton process. The quenching experiments showed that OH radical played a crucial role in the degradation of AR97 by Fe3 O4 /H2 O2 /OA/UV system. Benefiting from the high catalytic activity and easy magnetic separation, the prepared Fe3 O4 nanoparticles revealed good stability and reusability even after five consecutive cycles. This work offers a sustainable and effective way to recycle iron rust waste into an efficient catalyst for the degradation of organic contaminants in water. Graphical Abstract: ga1 Highlights: Different iron oxides were successfully synthesized from iron rust waste. The catalytic activity of iron oxide is affected by its crystal structure, size and morphology. Fe3O4 nanoparticles show a good efficiency for degradation of AR97. Oxalic acid enhanced the degradation of AR97 in the heterogeneous photo Fenton system. The mineralization of organic matter is strongly involved during this photo-Fenton process.